Perilaku Kepemimpinan Umar Abdul Azis (Khalifah Umayyah) Dalam Sistem Pemerintahan Islam - Yeni Sri Lestari (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
with the current government system by other models of leaders. This discussion is considered important for two reasons, firstly the government system in Indonesia which is the majority led by Muslim leaders no longer heed Islamic values and leadership which can improve the welfare of the community in the economic, political and social fields. The results of the study found Umar Abdul Aziz's behavior in governing brought many positive changes for the Umayyads during Umar's reign. Some positive aspects are often found in development in the political, economic and social fields. In some countries which are currently led by a Muslim, they should be able to make Umar's leadership model as an example.